Centralized procurement and delivery times: Evidence from a natural experiment in Italy - Robert Clark; Decio Coviello; Adriano de Leverano (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We study how delivery times and prices for hospital medical devices respond to the introduction of centralized procurement. Our identification strategy leverages a legislative change in Italy that mandated centralized purchases for a sub-set of devices. The statutory centralization generated a reduction in prices and an increase in delivery times for centralized purchases relative to non-centralized purchases. We use data on quantities and on suppliers to discuss the mechanisms potentially underlying our findings.
Keywords: D44; H51; H57; I18; 330; Public Procurement; Centralization; Medical Devices; Delivery Times; Bulk Purchasing